Climate Change and Energy Consumption Patterns in Thailand: Time Trends During 1988-2013 - Yuaningsih, Lilis; Febrianti, R. Adjeng Mariana; Kamran, Hafiz Waqas (International Journal of Energy Economics and Policy, 2020)
In traditional context, fossil fuel energy consumption is observed as non-renewable sources and contributing its major part for the energy source in the world economy. However, a new term under the title of renewable energy source is also examined and studied too. The focus of this paper is to investigate the impact of fossil fuel energy and renewable energy sources on the factor of climate change. For the measurement of climate change, overall six dimensions were added in the empirical analyses. The time period for the study was 1987 to 2013 and data was collected from World Development Indicator WDI. Findings for the regression analyses reveal that climate change in terms of CO2 emissions from liquid fuel consumption (kt) or C1 is directly influenced by both fossil and renewable energy, and same trend is found for CO2 emissions (kt); C2. Meanwhile, the third indicator of climate change C3 or CO2 emissions (kg per 2010 US of GDP) is negatively affected by renewable energy. Furthermore, C4 (CO2 emissions from gaseous fuel consumption (% of total)) is directly influenced by both of the energy sources in Thailand. Additionally, the trends in C5 is found to be positively determined by both fossil fuel and renewable energy, while their negative and significant impact is observed for C6; CO2 emissions from transport (% of total fuel combustion). Future research studies may consider the sub division of energy sources in both public and private sectors. Keywords: Fossil fuel, renewable energy, climate change, carbon emission, Thailand. JEL Classifications: Q54, Q15, Q56, Q18 DOI: https://doi.org/10.32479/ijeep.10695